PENYIMPANGAN ASAS NON-RETROAKTIF DALAM PENGADILAN HAM AD HOC DARI PERSPEKTIF HAM - SHINTA AGUSTINA; SISKA ELVANDARI; LUCKY RASPATY (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
Ad Hoc Human Rights Court is regulated in Article 43 paragraph (1) Human Rights Court Law, which is established with the aim of providing justice for victims of gross human rights violations that has occurred before the Law was enacted. However, the provision is deemed to be violating human rights itself since it is against the Article 281, which regulates the right not to be prosecuted based on retroactive laws. Besides, it is also contrast to the principle of non retroactive, as one of basic principles in criminal law. The practices of human rights enforcement in Indonesia and the international world accept that violation on the basis of justice and the Human Rights instruments which provide the possibility of a deviation of the Human Rights implementation. The deviation is also justified only for the most serious crimes which become the concern of the international world, that is gross Human Rights violations in the form of genocide and crimes against humanity.